Effect of Serratia entomophila and diazinon applied with seed against grass grub populations on the North Island volcanic plateau - Zydenbos, S.M.; Townsend, R.J.; Lane, P.M.S.; Mansfield, S.; O?Callaghan, M.; van_Koten, C.; Jackson, T.A. (New Zealand Plant Protection, 2016)
The bacterial biocontrol agent Serratia entomophila and the insecticide diazinon were applied as separate granular formulations with ryegrass seed and compared with a seedonly control treatment on three pastures of different ages and composition on the North Island volcanic plateau In the first 2 years diazinon and S entomophila significantly reduced healthy grass grub populations compared with the control However by the third year populations in the diazinon treatments had recovered and were significantly higher than in S entomophila or control plots Grass grub populations were reduced by disease outbreaks after S entomophila was applied which infected >40 of grass grub larvae in the treated plots in year two Bacterial extraction from soil a year after application confirmed establishment and persistence of S entomophila in treated plots Visual positive pasture growth responses were noted in both the S entomophila and diazinontreated plots